FROM ALIENATION TO YOUTH PARTISANSHIP: Systematic Analysis of Research on the Change of Youth Participatory Culture in Serbia - Vranic, Bojan M (Politeia, 2025)
The paper explores changes in the voting habits of young people and changes in the level of participation and political mobilization in Serbia. As a case study, it takes the period between November 2024 and May 2025, marked by massive student university blockades and the organization of several social protests. The aim of the paper is to identify, through a systematic analysis of available surveys of young people’s attitudes conducted between 2018 and 2024, the factors that have led to increased youth participation in political activities. The paper assumes the thesis that the case study of Serbia is an important social moment in which a generational shift of political elites is taking place, from those who promote security as the dominant social value to those who promote the issue of a well-governed society.